Measles virus nucleocapsid protein modulates the Signal Regulatory Protein-β1 (SIRPβ1) to enhance osteoclast differentiation in Paget's disease of bone - Sundaram, Kumaran; Sambandam, Yuvaraj; Shanmugarajan, Srinivasan; Rao, D. Sudhaker; Reddy, Sakamuri V. (Bone Reports, 2017)
Paget's disease of bone (PDB) is a chronic localized bone disorder in an elderly population. Environmental factors such as paramyxovirus are implicated in PDB and measles virus nucleocapsid protein (MVNP) has been shown to induce pagetic osteoclasts (OCLs). However, the molecular mechanisms underlying MVNP stimulation of OCL differentiation in the PDB are unclear. We therefore determined the MVNP regulated gene expression profiling during OCL differentiation. Agilent microarray analysis of gene expression identified high levels of SIRPβ1 (353-fold) expression in MVNP transduced human bone marrow mononuclear cells stimulated with RANKL. Real-time PCR analysis further confirmed that MVNP alone upregulates SIRPβ1 mRNA expression in these cells. Also, bone marrow mononuclear cells derived from patients with PDB showed high levels of SIRPβ1 mRNA expression compared to normal subjects. We further show that MVNP increases SIRPβ1 interaction with DAP12 adaptor protein in the presence and absence of RANKL stimulation. shRNA knockdown of SIRPβ1 expression in normal human bone marrow monocytes decreased the levels of MVNP enhanced p-Syk and c-Fos expression. In addition, SIRPβ1 knockdown significantly decreased MVNP stimulated dendritic cell-specific transmembrane protein (DC-STAMP) and connective tissue growth factor (CTGF) mRNA expression during OCL differentiation. Furthermore, we demonstrated the contribution of SIRPβ1 in MVNP induced OCL formation and bone resorption. Thus, our results suggest that MVNP modulation of SIRPβ1 provides new insights into the molecular mechanisms which control high bone turnover in PDB.